A PANDEMIA E A URGÊNCIA DE MEDIDAS PARA INCLUSÃO DIGITAL - Marcela Azarias Rodrigues; Thaís e Silva Albani; Daniela Hruschka Bahdur (TRF2, 2020)
This paper aims to examine how digital inclusion can be understoodas a right attached to human dignity, being grounded in a context in which relationships are increasingly dependent on technological tools. It is also intended to develop an approach that takes into account the current pandemic of COVID-19 disease, which has made the use of technological devices even more necessary for communication and access to basic services, as a result of the social distancing measures adopted to confront the new coronavirus. From this analysis, it is intended to verify some ways in which digital exclusion manifests itself in the context of the pandemic and how it becomes essential to recognize digital inclusion as a fundamental right. For this, the study will be developed through the deductive method, in a qualitative approach. Bibliographic and documental research will be carried out, by means of books, scientific articles and data extracted from research related to the subject discussed herein